2009
DOI: 10.1590/s1679-62252009000300018
|View full text |Cite
|
Sign up to set email alerts
|

The more stirring the better: cichlid fishes associate with foraging potamotrygonid rays

Abstract: One hunting tactic of freshwater rays (Potamotrygonidae), termed "undulate the disc and stir substrate", is here reported to attract cichlids at two sites in the upper Paraná River. The ray species involved in such association are Potamotrygon falkneri and P. motoro, whose activity attract four cichlid species, namely Crenicichla britskii, Satanoperca pappaterra, Cichla kelberi, and Geophagus proximus, the two latter non-native species to the study area. The cichlids approach a ray when it begins to stir the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although such interactions are commonly recorded in marine environments (Strand, 1988;Lukoschek & McCormick, 2000;Sazima et al, 2006;Sazima et al, 2007), there are studies on such interactions in tropical freshwater environments as well, mostly in tropical waters (e.g., Baker & Foster, 1994;Leitão et al, 2007;Ott, 2007;Teresa & Carvalho, 2008;Garrone-Neto & Sazima, 2009;Teresa et al, 2011). Despite efforts to describe this type of association, knowledge of its modulating factors is still incipient (see Sazima et al, 2005;Krajewski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although such interactions are commonly recorded in marine environments (Strand, 1988;Lukoschek & McCormick, 2000;Sazima et al, 2006;Sazima et al, 2007), there are studies on such interactions in tropical freshwater environments as well, mostly in tropical waters (e.g., Baker & Foster, 1994;Leitão et al, 2007;Ott, 2007;Teresa & Carvalho, 2008;Garrone-Neto & Sazima, 2009;Teresa et al, 2011). Despite efforts to describe this type of association, knowledge of its modulating factors is still incipient (see Sazima et al, 2005;Krajewski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although substrate disturbance is one of the most important predictors for the species acting as nuclear (Sazima et al 2006, Krajewski 2009, Teresa et al 2011 and tetras are opportunistic foragers (Sazima 1986, Teresa & Carvalho 2008, a typical nuclearfollower feeding association and interactions of characiform fishes with potamotrigonid rays had not been described under natural conditions. The only record related to this subject was made by Garrone Neto & Sazima (2009a), that reported feeding associations among two species of Potamotrygonidae and cichlids in a disturbed stretch of the Upper Paraná River, Southeastern Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…The following behavior comprises one or a group of individuals that excavate or disturb the substrate while foraging, and one or more opportunistic species that capitalize on the small organisms and other food types displaced by the foraging activity of the former (Strand 1988, Lukoschek & McCormick 2000. This type of interespecific interaction has been widely described to teleost fishes in marine environments (see Strand (1988) and Sazima et al (2006) for overviews), although a few instances are reported from neotropical freshwater habitats that provide conditions for underwater observations (Sazima 1986, Baker & Foster 1994, Casatti & Castro 1998, Sabino & Zuanon 1998, Sabino 1999, Carvalho et al 2003a, Garrone Neto & Sazima 2009a, Leitão et al 2007, Teresa & Carvalho 2008, Teresa et al 2011.…”
Section: Introductionmentioning
confidence: 91%
“…Potamotrygonids are carnivorous and prey on a variety of animals Moro et al, 2012;Shibuya et al, 2012). Their hunting tactics include some with high metabolic costs, e.g., undulating their disc margins to disturb the substrate and uncover hidden prey or charging prey concentrated in shallow water (Garrone-Neto & Sazima, 2009a;Garrone-Neto & Sazima, 2009b;Garrone-Neto & Uieda, 2012). Thus, it is possible to summarise the activity patterns of potamotrygonids in accordance with Gray's scale (Gray, 1954), which includes active, intermediate, and sluggish activity levels.…”
Section: Introductionmentioning
confidence: 99%